130 Effects of a multi-strain Bacillus subtilis-based direct-fed microbial on immunity markers, intestinal morphology, and microbial communities in diets fed to weanling pigs. (30th November 2020) - Lewton, Jaron R; Woodward, Adrienne; Moser, Ronny; Thelen, Kyan M; Moeser, Adam J; Trottier, Nathalie; Tempelman, Robert; Rozeboom, Dale W
Abstract: The objective of this experiment was to evaluate the effects of a multi-strain Bacillus subtilis-based direct-fed microbial (DFM) on intestinal mucosal and blood plasma immunological markers, intestinal morphology, and microbiota of nursery pigs as indicators of health status. Eighty pigs, of equal number of barrows and gilts (initial BW: 6.99 ± 1.67 kg), weaned at 21 ± 1 days of age were randomly allotted to sixteen pens, with five pigs per pen. Two dietary treatments were implemented, a basal control (CON) and a control plus DFM (DFM). Both diets were corn, soybean meal, and distillers dried grains based, formulated to meet all or exceed all nutritional requirements, and manufactured on site. Diets were fed for 42 days. On d 21 and 42 of the experiment, one pig per pen was randomly selected and euthanized, with equal number of males and females represented. Blood samples were collected prior to euthanasia for assessment of plasma levels of immunoglobin A (IgA) and intestinal fatty acid binding protein. Segments of the gastrointestinal tract including duodenum, jejunum, ileum, ascending and distal colon were removed for analysis of intestinal morphology, microbial communities, and levels of interleukin 6, interleukin 10 (IL-10), and tumor necrosis factor alpha. Jejunal villus height was greater (P = 0.02) in DFM compared with CON (422 vs. 385 ± 10 µm, respectively) and ascending colon crypt depth tended to be greater (P = 0.10) on d 21 (373 vs. 337 ± 14 µm, respectively). Compared to CON, DFM tended to increase IgA (P = 0.06) on d 21 (0.34 vs. 0.54 ± 0.07 mg/mL, respectively) and tended to increase IL-10 (P = 0.12) on d 42 (133 vs. 237 ± 49 pg/mL, respectively). Addition of a multi-strain Bacillus subtilis-based DFM may have a potential early benefit to nursery pig health status.